Dukungan Istri, Peran Petugas KB dalam Peningkatan Partisipasi Pria dalam Keluarga Berencana - Surya Dewi Puspita (Puslitbang Sinergis Asa Professional, 2019)
The Family Planning Programme in Indonesia is dominated by women. In year 2016, the active male participant of contraception acceptor in Jember was 1,08%. This low number achievement was occurred due to the lack of support from their wife and the family planning volunteer. The main purpose of this study was to determine the effect of adequate support from wife and family planning volunteer could increase the men participation. The cross-sectional design was used in statistical analysis and the multistage of random sampling was used as sampling technique. The samples are 380 productive men. Data were collected by fulfilling questionnaires and it analysed by logistic regression with 0,05 or ɑ=95% were significantly different. The results show there is a significant different in support of wife (p=0,000) and family planning volunteer (p=0,000) respectively. The results of research related to wife support are respondents with wives who do not support male contraception as many as 275 respondents (99%) do not participate in the family planning program and respondents with wives who support male contraception are 36 respondents (35.3%) participate in large family planning programs. support respondents to use male contraception. The results of the study related to the role of officers namely the majority of respondents with the role of passive officers as many as 214 respondents (99%) did not participate in the family planning program and respondents with the role of active officers as many as 36 respondents (22%) participated in large family planning programs the role of passive officers.